DIGITAL TO THE PROCESS OF PHYSICS EDUCATION IMPLEMENTATION OF TECHNOLOGIES AND MODERN METHODS INFRASTRUCTURE THROUGH INNOVATION (Scientific journal of the Fergana State University, 2024)
within the globally acclaimed general education system, training sessions are structured to integrate theory and practice, particularly focusing on researching the methodological foundations of integrating theory and practice in physics education. These activities aid students in comprehending various aspects of modern scientific and technical advancements, environmental issues, methods of sustainable natural resource management, principles of a healthy lifestyle, and fundamentals of financial and economic literacy, which they can apply in their everyday lives. This integrated approach serves as a vital system aimed at nurturing essential skills and qualifications.The concept of developing the public education system of the Republic of Uzbekistan until 2030 outlines the current status of physical education and identifies existing issues. Recognizing the demands of the times, STEAM (Science, Technology, Engineering, Arts, and Mathematics) has emerged as a pivotal subject in international student education. However, there’s a noted lack of emphasis on integration and practical approaches, as well as inadequate development of teaching materials and methodological support for physics, including multimedia products and didactic materials.To address these challenges and promote the integration of theory and practice in physics education at secondary schools, the development and implementation of a virtual package of demonstration experiments are proposed. This initiative serves as a crucial foundation for nurturing students’ creativity and fostering their interests in physics. Conducting demonstration experiments in physics typically requires significant equipment, and the process of replacing damaged equipment can be time-consuming. Therefore, the aim is to develop virtual demonstration experiments as an alternative solution. The creation of such virtual experiments is anticipated to alleviate the aforementioned issues. Furthermore, ensuring that all educational institutions in the republic have access to an adequate supply of demonstration experiments without incurring additional financial burdens is expected to enhance the quality of physics instruction.